ANALISIS HUBUNGAN MOTIVASI INTERNAL DAN EKSTERNAL TERHADAP DISIPLIN KERJA KARYAWAN - Mayla Surveyandini; Kaboel Budiono (Majalah Imiah Manajemen & Bisnis, 2020)
Research titled "Analysis of Internal and External Relationships Motivation Against Employee Discipline in American English Course Purwokerto" aims to analyze the relationship between internal and external motivation to discipline employees. From the results of this study are expected to contribute positively both to the company and other parties. Use of sampling techniques for sampling saturated as the number of samples studied population is 15 people. Analysis of the data used is multiple linear regression. From the calculations, the conclusion that there is no significant positive relationship between internal and external motivation to discipline employees. This study has several limitations that only focuses on one company alone and targeted research is limited to employees in American English Course. Future research may consider any other company than in the service sector, such as electronics companies, automotive, banking, and others. Need to put together combinations of other variables that have not been included in this study